AN ANALYSIS OF THE COHESION AND COHERENCE OF STUDENTS’ DESCRIPTIVE WRITING - Saragih, Enni Erawati; Septiani, Siti Nuraeni (ENGLISH JOURNAL, 2017)
This study was conducted to describe the cohesion and coherence of descriptive paragraphs written by the students of Senior High School in Bogor. To meet this purpose, 30 students were chosen as the participants of this study. The data were collected through administering writing task. The data analyzed qualitatively on the basis of Halliday and Hasan’s theory of cohesion and analyzing coherence by Lautamatti’s topical structure analysis theory of progression.The result showed that reference was the types of cohesive devices that highly used by the students to build cohesion in their descriptive paragraphs, followed byconjunction,reiteration, ellipsis and collocation, and substitution. The types of topical progression used by the students to build their descriptive writing were parallel progression, sequential progression, and extended parallel progression. The highly used of parallel progression indicates that the overall view of the topical progression of the students’ descriptive texts followed a dominant use of parallel progression, realized by the repetition the/it in the beginning sentence as the sentence topic through their story. The result of this research indicates that the students in Senior High School Bogor can build cohesion and coherence devices on their descriptive paragraphs. It can be seen by the data that five of six types of cohesion devices appeared in their paragraphs, and also all of topical progression were used on their writing.The English teachers have to be competent in evaluating the cohesion and coherence of students writing in order to be better.